Amalan sedutan endotrakea dalam kalangan jururawat dl unit rawatan rapi Hospital Universiti Sains Malaysia (HUSM) - Salleh, Nurul Ainil Wahedah Mohamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2006)
Endotracheal suctioning is a procedure to retnove secretion and mucous from the respiratory tract. However, this procedure contributes cotnplications to patient such as hypoxia, hypoxetnia, trauma to the tracheal tissue, cardiac arrhythmias and also raises intracranial pressure. The aim of the study were to explore nurse's practice in performing endotracheal suctioning in the Intensive Care Unit HUSM and to investigate the changes of Sp02 level, H/R and MAP before, immediately after, 5 and 10 minutes after suctioning. Thirty (30) nurses were involved in the study. A checklist was used to observe the suctioning practices of the nurses. Changes of the Sp02, H/R and MAP level were collected from patients' record and cardiac monitor. The study shows that there were an increased or decreased of Sp02 level, H/R and MAP before, immediately after, 5 minutes and 10 minutes of endotracheal suctioning. Used of vacuum pressure for suctioning and suctioning time practice by nurses did not met the standard requirement as suggested by previous research. Complications from improper suctioning technique could be prevented with the practice of recommended endotracheal suctioning techniques.